استحداث أسلوب المزاد الإلكتروني كإجراء اسثنائي لإبرام الصفقات العمومية بالطريقة الإلكترونية في التشريع الجزائري - بوزيد، خالد Bouzaidi, Khaled (جامعة زيان عاشور الجلفة, 2022)
يعد أسلوب المزاد الإلكتروني العكسي من أهم المستجدات التي أقرها المشرع الجزائري في المنظومة القانونية للصفقات العمومية، تماشيا مع مشروع رقمنة الصفقات العمومية الذي تجسد في الجزائر من خلال إنشاء البوابة الإلكترونية للصفقات العمومية، حيث تم اعتماد هذا النمط الجديد من التعاقد الإداري الإلكتروني بموجب المرسوم الرئاسي رقم 15-247، من خلال منح المصلحة المتعاقدة سلطة إبرام صفقات اقتناء اللوازم والخدمات العادية بالطريقة الإلكترونية وفق إجراء المزاد الإلكتروني العكسي. The reverse electronic auction method is one of the most important developments approved by the Algerian legislator in the legal system for public markets, in line with the project of digitizing public deals that was embodied in Algeria through the establishment of the electronic portal for public markets, where this new style of electronic administrative contracting was approved by Presidential Decree No. 15-247, by granting the contracting authority the authority to enter into transactions for the acquisition of ordinary supplies and services by electronic method according to the reverse electronic auction procedure.
Keywords: الصفقات العمومية -- المزدات الإلكترونية -- القانون الجزائري